Life in Health 2021: Research and Practice: Proceedings of the International Conference held on 9–10 September 2021 - Štveráková, Tereza; Jačisko, Jakub; Busch, Andrew; Šafářová, Marcela; Kolář, Pavel; Kobesová, Alena; Kachlík, Petr; Hřivnová, Michaela; Slaná Reissmannová, Jitka; Sofková, Tereza; Cichá, Martina; Marciánová, Vladislava; et al. (Masaryk University Press, 2021)
This proceedings contain a selection of papers from the international interdisciplinary conference Life in Health 2021, which took place from 9 to 10 September 2021 in the Czech Republic at the Faculty of Education, Masaryk University. The papers focus on general as well as specific approaches to public health protection and promotion. The findings presented are based on research data and are applicable in health education and general education of children and the whole population.